The Expansion of Palm Oil Plantation and Changes of Rural Social Ecology - Hidayah, Nursantri; Dharmawan, Arya Hadi; Barus, Baba (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTThe biggest threat to Indonesian forest is the rise of new palm oil plantation. Indonesia ranked the top by the quantity and rate of expansion of oil palm cultivation. Riau ranked first with a contribution of 29 percent of the total national production of palm oil. The rate of expansion of oil palm plantations such as by land use change forest area, land of community, and farmland. Demand for land to the expansion of oil palm plantations in Riau Province continues to increase is so that has triggered high rates of conversion of land into oil palm plantations, this expansion HAS ALSO led to a conservation area. Many cases of illegal land conversion is done as occurs in protected areas and conservation. Tesso Nilo National Park is one of the National Park in Riau province precisely in Pelalawan and Indragiri Hulu does not escape from the activity of land conversion for oil palm plantations. Oil palm expansion has led to various effects such as changes in the landscape, the relocation of land and natural resources, changing economic and social. This research was conducted with the aim of identifying changes in land use landscape surrounding Tesso Nilo National Park, the changes livelihoods of local communities and the vulnerability of farm Households. Studies conducted in the village conservation area affected by oil palm expansion. Data were Analyzed descriptively by using spatial analysis and livelihood systems. From the results of the research Noted that oil palm expansion in Tesso Nilo has the caused massive degraded forests, forest cover is left now only about 20 percent. The pattern of the community living around the area turn out to be are relatively homogeneous with one source of income is from oil palm plantations. This causes people to be vulnerable to a crisis when palm oil prices declined. The high food consumption from the dependent communities will complicate the supply from outside the community when revenues decline. For the sustainability of the region need more intensive management area so that the destruction of the forests as a result of actions of this expansion can be overcome and potential conflicts between the oil palm and food crops in the future must be anticipated so there is no economic vulnerability of farm households.Keywords: ecology landscape changes, expansion of oil palm, livelihood systemsABSTRAKAncaman terbesar terhadap hutan Indonesia adalah maraknya pembukaan perkebunan kelapa sawit baru. Indonesia menduduki peringkat teratas berdasarkan kuantitas perluasan perkebunan dan laju penanaman kelapa sawit. Riau berada di peringkat pertama dengan kontribusi sebesar 29 persen terhadap total produksi minyak sawit nasional.Laju perluasan perkebunan kelapa sawit diantaranya dengan jalan mengalihfungsikan kawasan hutan, kebun rakyat, dan lahan pertanian. Permintaan lahan untuk ekspansi perkebunan sawit di Provinsi Riau terus meningkat sehingga telah memicu tingginya angka konversi lahan menjadi perkebunan kelapa sawit, ekspansi ini juga sudah mengarah ke kawasan konservasi. Banyak kasus konversi lahan dilakukan secara illegal seperti yang terjadi pada kawasan lindung dan konservasi. Taman Nasional Tesso Nilo  (TNTN) adalah salah satu Taman Nasional di Provinsi Riau tepatnya di Kabupaten Pelalawan dan Kabupaten Indragiri Hulu yang tidak luput dari aktivitas konversi lahan untuk perkebunan kelapa sawit. Ekspansi kelapa sawit telah menimbulkan berbagai dampak seperti terjadinya perubahan bentang alam, relokasi tanah dan sumber daya alam, perubahan ekonomi dan perubahan sosial. Penelitian ini dilakukan dengan tujuan mengidentifikasi perubahan penggunaan lahan disekitar lanskap Taman Nasional Tesso Nilo, perubahan sistem naflah masyarakat lokal dan kerentanan rumah tangga petani. Studi dilakukan di desa sekitar kawasan konservasi yang terkena dampak ekspansi kelapa sawit. Data dianalisis secara deskriptif dengan menggunakan analisis spasial dan analisis sistem penghidupan. Dari hasil penelitan diketahui bahwa ekspansi kelapa sawit di sekitar Taman Nasional Tesso Nilo telah menyebabkan hutan terdegradasi secara masif, tutupan hutan yang tersisa saat ini hanya sekitar 20 persen. Pola nafkah masyarakat sekitar kawasan berubah menjadi cenderung homogen dengan satu sumber nafkah yaitu dari perkebunan kelapa sawit. Ini menyebabkan masyarakat menjadi rentan terhadap krisis ketika harga kelapa sawit menurun. Tingginya konsumsi pangan masyarakat yang tergantung pasokan dari luar akan menyulitkan masyarakat ketika pendapatan mengalami penurunan.Bagi keberlanjutan pengembangan wilayah perlunya pengelolaan kawasan yang lebih intensif sehingga kerusakan hutan akibat tindakan ekspansi ini bisa diatasi dan potensi konflik antara pihak perkebunan kelapa sawit dan pertanian tanaman pangan kedepan harus diantisipasi sehingga tidak terjadi kerentanan ekonomi rumah tangga petani.Kata kunci: perubahan lanskap ekologi, ekspansi kelapa sawit, sistem penghidupan